Utilization of Camera Vision to Monitor Production Line Operator Learning Curve - Nur Sabania, Suaib; NOR SHAHIDA, MOHD SHAH; Amirul Syafiq, Sadun (Progress in Engineering Application and Technology, 2024)
The increasing demand for efficiency in modern manufacturing requires advanced methods for monitoring and optimizing production line performance. Traditional approaches often fail to provide real-time insights into operator proficiency, resulting in delayed responses and suboptimal training interventions. This research addresses these challenges by leveraging camera vision technology to enhance the assessment and improvement of operator learning curves. The primary objective is to develop and implement a real-time monitoring system that captures and analyzes production line operator activities using camera vision, providing timely and accurate assessments to design targeted training programs. The system employs high-resolution cameras and computer vision techniques to monitor and evaluate operator movements, improving the accuracy and timeliness of proficiency assessments. Results indicate significant improvements in operator learning curves and smoother motion patterns, demonstrating the system's effectiveness. Real-time feedback enabled immediate adjustments and targeted training, enhancing overall production line efficiency. The successful implementation of this technology promises increased efficiency and productivity in manufacturing, showcasing its transformative impact on operator performance assessment.